(untitled) (Research, Society and Development, 2022)
Vague language is observed in language elements that make the meaning unclear. In this pragma-linguistic paper, the authors aim to review the different proposed theories and definitions of vague language that were suggested in the middle of the past century. Through discourse analysis of vague usage, authors justify politeness in communication, gender, culture, press releases, and education. Authors found that there is dissatisfaction among speakers with describing the terminologies and possible meanings of a text. Another promising finding is that the vague language creates controversial semantics and pragmatics discussions among discourse genre specialists. The listener’s comprehension of quantifiers and linguistic approximators is limited to an exact number of vague words; thus, speakers are strongly recommended to avoid using vagueness in their speeches.